Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

A field system to deliver desired O-3 concentrations in leaf-level gas exchange measurements: Results for Holm oak near a CO2 spring - Grulke, N. E.; Paoletti, E. (PHYTON-ANNALES REI BOTANICAE, 2005)
Conventional gas exchange systems adsorb ozone (O-3) despite attempts to saturate the system prior to measurements. A steady-state, open photosynthetic system was designed and used in the field to supply a small leaf cuvette with conditioned air stream (growth CO2 concentrations, humidified, cooled) and augmented with either background or elevated O-3. Two innovations led to success: 1) supplying the cuvette with cooled air instead of Peltier cooling within the cuvette; and 2) using a custom-designed, low flow (capable of 100 seem), fast response (20 S) O-3 monitor. We tested whether elevated CO2 would alter stomatal response to short term, steady state elevated O-3. Holm oak (Quercus ilex L., Fagaceae), an evergreen broadleaf tree growing near a geothermal CO2 vent, has been exposed over its lifetime to a gradient of CO2 concentrations. We chose trees in areas averaging 450 mu l 1(-1) (low background CO2) and 1500 mu l 1(-1) (super-elevated CO2). Background O-3 exposure at this site is moderate (10 am to 5 pm averages of 62 nl 1(-1) in June). We measured gas exchange at the growth CO2 levels, and at ambient O-3 or 1.7x ambient O-3 concentrations. At low background CO2, short term elevated O-3 depressed foliar transpiration. Because there was little concurrent change in net assimilation, instantaneous transpiration efficiency was increased. At super-elevated CO2, short term elevated O-3 did not affect foliar transpiration. Because there was a concurrent decrease in net assimilation, instantaneous transpiration efficiency was decreased at elevated CO2 and O-3.
The following values have no corresponding Zotero field: pub-location: WIENER STRASSE 21-23, A-3580 HORN, AUSTRIA publisher: FERDINAND BERGER SOEHNE
Keywords: Carbon dioxide; instantaneous transpiration efficiency; ozone exposure; Quercus ilex

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) - Manes, F; Vitale, M; Donato, E; Paoletti, E (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2
Keywords: CO2 (voyant); Holm oak; Net photosynthesis; ozone exposure; peroxidase activity; Transpiration